Prevalence of Insomnia and Related Factors Among Cancer Outpatients in China - Zhao K; Yu Z; Wang Y; Feng W (Nature and Science of Sleep)
Kuan Zhao,1,2,* Ze Yu,1,2,* Youyang Wang,1,2 Wei Feng1,2 1Department of Psychological Medicine, Fudan University Shanghai Cancer Center, Shanghai, 200032, People’s Republic of China; 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Feng, Department of Psychological Medicine, Fudan University Shanghai Cancer Center, 270 Dongan Road, Shanghai, 200032, People’s Republic of China, Email ffww06@163.comBackground: The incidence of insomnia in cancer patients is significantly higher than in the general population. Chronic insomnia imposes pronounced physical and psychological burdens on cancer patients, affecting their quality of life and survival rate. This study aims to investigate insomnia in cancer patients and further analyze potentially related factors.Methods: Oncology outpatients treated at Fudan University Shanghai Cancer Center were consecutively recruited. Demographic information and clinical features, such as type of cancer and treatment status, were collected. Insomnia was assessed using the Insomnia Severity Index (ISI).Results: A total of 146 patients participated in the study, with the majority suffering from breast tumors (40.4%), gastrointestinal tract tumors (18.5%), and endocrine tumors (5.8%). Among these patients, 25 (17.1%) did not report insomnia, 69 (47.3%) had subclinical insomnia, and 52 (35.6%) reached the level of clinical insomnia. Older patients aged 41– 50 years (Estimate = − 3.49, 95% CI, − 6.99 to 0.00, p = 0.05) and those with higher education levels (Estimate = − 2.72, 95% CI, − 4.88 to − 0.55, p = 0.01) were less likely to have higher ISI total scores. In contrast, undergoing chemotherapy (Estimate = 3.86, 95% CI, 0.53 to 7.19, p = 0.02) was associated with higher ISI total scores. Gender, age, education, treatment modalities correlated with ISI subitem scores.Conclusion: The prevalence of insomnia is higher in oncology patients and is associated with gender, age, education, tumor type, and treatment modality. Screening and interventions for insomnia should be emphasized in the whole-course management of oncology patients.Keywords: cancer, outpatient, treatment, insomnia, insomnia severity index